2018
DOI: 10.15296/ijwhr.2018.55
|View full text |Cite
|
Sign up to set email alerts
|

Physical Health and Maternal-Fetal Attachment among Women: Planned Versus Unplanned Pregnancy

Abstract: Introduction Planned pregnancy is an important indicator of improving the health status of mothers and newborns, as today unplanned pregnancy is a public health indicator (1). There are 2 types of unplanned pregnancies; first, the pregnancy which happens sooner than intended pregnancy time called mistimed pregnancy. And the second type which is unintended pregnancy, when a woman has no decision to have a baby in the future (2-4). Pregnancy and childbirth are joyful experiences for women (4). This event raises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
2
6
0
1
Order By: Relevance
“…So, planned pregnancies can increase the prenatal attachment level. Previous studies also support this finding (Ossa et al, 2012;Karakoç and Ozkan, 2017;Pakseresht et al, 2018;Coşkun et al, 2019;Karabulutlu et al, 2020;Çelik and Güneri, 2020). Pregnant women with unplanned pregnancies fall behind in receiving health care services, encounter more risky situations, have more complications, and have less self-care (Boden et al, 2015;Goossens et al, 2016;Srewart et al, 2016;Canella et al, In this regards, Zibellina et al highlighted that a planned pregnancy and women's level of education has great importance for the increase of prenatal attachment and a healthy pregnancy.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…So, planned pregnancies can increase the prenatal attachment level. Previous studies also support this finding (Ossa et al, 2012;Karakoç and Ozkan, 2017;Pakseresht et al, 2018;Coşkun et al, 2019;Karabulutlu et al, 2020;Çelik and Güneri, 2020). Pregnant women with unplanned pregnancies fall behind in receiving health care services, encounter more risky situations, have more complications, and have less self-care (Boden et al, 2015;Goossens et al, 2016;Srewart et al, 2016;Canella et al, In this regards, Zibellina et al highlighted that a planned pregnancy and women's level of education has great importance for the increase of prenatal attachment and a healthy pregnancy.…”
Section: Discussionsupporting
confidence: 70%
“…A review of the literature showed that a higher prenatal attachment level is related to positive pregnancy, labor, and postpartum results. Pregnant women with a higher prenatal attachment have a healthier pregnancy, less labor-related fear, and a lower rate of depression and anxiety in the postpartum period (Salehi and Kohan, 2017;Coşkun et al, 2019;Bakır and Sarızayim, 2020;Pakseresht et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Especially age > 35 years, higher educational level and history of depression were associated with prolonged ambivalent feelings towards the pregnancy. Since parents with ambivalent feelings towards the pregnancy may experience less connection with the fetus and newborn child [ 48 50 ], the results of this study suggests that additional support in bonding, attachment and parent-child interaction during and after pregnancy is recommended in this cluster [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from recent clinical trials indicate parent training interventions may also reduce parental depressive symptoms and improve children's outcomes (Beach & Whisman, 2012). However, it may be difficult to engage multi‐stressed families, such as those who are more likely to experience unintended pregnancies, in parent training interventions (Reyno & McGrath, 2006). Therefore, future research should seek to evaluate the efficacy of empirically supported parent training interventions (e.g., The Incredible Years, Webster‐Stratton & Reid, 2010; Parent Management Training‐Oregon Model, Patterson et al, 2010) to reduce parenting stress and depressive symptoms and promote positive parenting practices among families who have experienced unintended pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, their high-stress context increases risk for postpartum depression (Venkatesh et al, 2014). Women with unintended pregnancies tend to report less emotional attachment to their baby in pregnancy (Pakseresht et al, 2018) and tend to need more time to accept their pregnancy (Bajurna et al, 2014), which may each help explain their risk for depressive symptoms. Still, not all studies have found a significant association (Su, 2012), suggesting the need for further study of the association between pregnancy intention and maternal depressive symptoms.…”
Section: Pregnancy Intention Pregnancy Intention and Parenting Outcomesmentioning
confidence: 99%